1976
DOI: 10.1007/bf01971587
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory and related properties of 2-(2,4-dichlorophenoxy)phenylacetic acid (fenclofenac)

Abstract: Fenclofenac was shown to possess anti-inflammatory, antinociceptive and antipyretic properties as measured by tests in rats that detect clinically active compounds. In a chronic test for assessing anti-inflammatory activity (established adjuvant arthritis), it was approximately equipotent to alclofenac, fenoprofen calcium and phenylbutazone, more potent than acetylsalicylic acid and ibuprofen, but was less potent than diclofenac sodium, indomethacin, ketoprofen and naproxen. In contrast, the potency of fenclof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

1978
1978
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 15 publications
(12 reference statements)
1
9
0
Order By: Relevance
“…An analysis of the chemical nature of the labelled molecules in the different compartments of interest is in preparation. We have confirmed our previous observations concerning the specific biodistribution of acidic, antiinflammatory analgesics using near adult rats (120 g) at high, clearly anti-inflammatory doses (see also the data of Atkinson & Leach, 1976). Even at these doses considerably higher concentrations (for example, three times with indomethacin) of labelled drug were found in the inflamed paw compared with the control.…”
Section: Discussionsupporting
confidence: 90%
“…An analysis of the chemical nature of the labelled molecules in the different compartments of interest is in preparation. We have confirmed our previous observations concerning the specific biodistribution of acidic, antiinflammatory analgesics using near adult rats (120 g) at high, clearly anti-inflammatory doses (see also the data of Atkinson & Leach, 1976). Even at these doses considerably higher concentrations (for example, three times with indomethacin) of labelled drug were found in the inflamed paw compared with the control.…”
Section: Discussionsupporting
confidence: 90%
“…Firstly, fenclofenac failed to exert a significant inhibitory effect on carrageenin paw oedema at doses which markedly inhibit prostaglandin production induced by the same irritant. Secondly, fenclofenac and phenylbutazone were apparently equipotent as inhibitors of carrageenininduced prostaglandin release yet previous studies have shown that phenylbutazone was significantly more potent than fenclofenac in the carrageenin oedema test [9]. Thus it would appear that the anti-oedema activity of fenclofenac is mediated by either an additional or alternative mechanism which becomes operative at doses in excess of those required to suppress prostaglandin release.…”
Section: Discussionmentioning
confidence: 93%
“…It was, therefore, of interest to determine whether fenclofenac, a recently developed nonsteroidal anti-inflammatory agent [8,9], inhibited prostaglandin production and to ascertain whether such activity could account for its antiinflammatory properties. For this purpose, studies have been undertaken to see if fenclofenac lowers prostaglandin levels in rat inflammatory exudate and to compare such activity with that of standard drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Fenclofenac ( Fig. 1), a recently developed NSAAIA [10,11], appears to be qualitatively different from ASA in its effects on the gastric mucosa of guinea pigs when administered intragastrically [12]. Whereas at pH 7.4 ASA produced minimal mucosal cell exfoliation and shallow gastric erosions, fenclofenac induced marked cellular exfoliation but no erosions.…”
mentioning
confidence: 88%
“…However, many NSAAIAs, including ASA, indomethacin, phenylbutazone and fenclofenac, reduce elevated plasma fibrinogen levels in rats with adjuvant arthritis [11,21]. This raises the possibility that the apparently selective effect of alclofenac, fenclofenac and ICI 55,897 on ESR and related parameters in rheumatoid patients is merely a reflection of a higher level of anti-inflammatory activity and not of some novel antirheumatic action.…”
mentioning
confidence: 99%